2019
DOI: 10.5430/irhe.v4n2p25
|View full text |Cite
|
Sign up to set email alerts
|

More Than Meets the Eye: A Canadian Comparative Study on PowerPoint Use Among Post-Secondary Students With and Without Disabilities

Abstract: The present study set out to explore effective teaching techniques using PowerPoint for post-secondary students with disabilities by comparing their views to those of students without disabilities. 284 Canadian post-secondary social science students, 75 of whom self-reported a disability, were surveyed about what aspects of PowerPoint use helps them learn. The good news is that the results indicate many similarities between the views of students with and without disabilities. Although all students felt that ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 19 publications
1
14
0
Order By: Relevance
“…One difficulty students encountered relates to the timing of posting documents. Some students like to prepare for the class and need more than a few hours' notice regarding documents that need to be read before class (Fichten et al, 2019). Another common complaint relates to professors not seeing questions asked by their students in Zoom and Teams chats.…”
Section: Professors' Management Of the Coursementioning
confidence: 99%
“…One difficulty students encountered relates to the timing of posting documents. Some students like to prepare for the class and need more than a few hours' notice regarding documents that need to be read before class (Fichten et al, 2019). Another common complaint relates to professors not seeing questions asked by their students in Zoom and Teams chats.…”
Section: Professors' Management Of the Coursementioning
confidence: 99%
“…Although it has been suggested that Universal Design for Learning can be used to minimize academic accommodations (Gidden & Jones, 2021), there is little data to suggest that this is actually feasible in many institutions. Moreover, data show that fewer than 50% of students with disabilities register to receive accommodations both in Canada (Fichten et al, 2018;2019a) and America (Cohen et al, 2020;McGregor et al, 2016;Newman et al, 2016;Parsons et al, 2021). There are a variety of barriers to registering, as reviewed by Toutain (2019).…”
Section: Nature Of Accommodationsmentioning
confidence: 99%
“…Between 17% and 34% of post-secondary students in American (Canadian University Survey Consortium, 2020, 2021 and Canadian post-secondary institutions (Fichten et al, 2018(Fichten et al, , 2019a) have a disability. As in many other countries, Canadian four-year and two-year college students with disabilities are eligible for and utilize services and accommodations to provide them with an equal opportunity to demonstrate mastery of course materials.…”
Section: Introductionmentioning
confidence: 99%
“…It also allows learners to rewind, slow down, and replay content when needed (Dinmore, 2019). Slide presentations can benefit all learners as long as they are properly designed and verified using PowerPoint's accessibility checker (Fichten et al, 2019).…”
Section: Impact Of Technological Resources On Student's Learningmentioning
confidence: 99%